Deciphering the Nexus Between Renewable Energy Consumption and Environmental Pollution: A GMM Model Analysis Across Diverse Economies - Giang, Mai Huong; Tung, Truong Nhat; Trang, Nguyen Thi Thu; Giang, Phan Thi Linh; Ha, Tran Thi Ngoc; Nguyet, Ho Thi Minh (International Journal of Energy Economics and Policy, 2025)
Addressing green economic issues is crucial for reducing environmental pollution and fostering sustainable development. Green economics promotes sustainable practices, including renewable energy. While renewable energy reduces emissions and reliance on fossil fuels, its full environmental impact is not entirely understood. More academic research is needed to investigate these interactions and develop strategies to mitigate any adverse effects. This study examines the impact of renewable energy consumption on environmental pollution across 53 countries from 2009 to 2021. Utilizing the Generalized Method of Moments approach by Arellano and Bond (1991) with instrumental variables, the findings show that renewable energy consumption significantly reduces CO2 and GHG emissions. Furthermore, control variables including globalization, government spending, and COVID-19 reduce emissions, while economic growth increases them. The impacts also vary across different countries, highlighting the complexity of environmental issues. As a result, this study proposes policy recommendations to improve sustainable environmental development.